2015
DOI: 10.3390/en8065459
|View full text |Cite
|
Sign up to set email alerts
|

Dehydriding Process and Hydrogen–Deuterium Exchange of LiBH4–Mg2FeD6 Composites

Abstract: Abstract:The dehydriding process and hydrogen-deuterium exchange (H-D exchange) of xLiBH4 + (1 − x)Mg2FeD6 (x = 0.25, 0.75) composites has been studied in detail. For the composition with x = 0.25, only one overlapping mass peak of all hydrogen and deuterium related species was observed in mass spectrometry. This implied the simultaneous dehydriding of LiBH4 and Mg2FeD6, despite an almost 190 °C difference in the dehydriding temperatures of the respective discrete complex hydrides. − was replaced by D atoms im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Ghaani et al reported a composite reaction similar to that shown in Equation (2) in the LiBH4-rich composition [13,19]. Our results demonstrate that the reaction between LiBH4 and Mg2FeH6 was stoichiometric and did not degrade when excess LiBH4 or Mg2FeH6 was present.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Ghaani et al reported a composite reaction similar to that shown in Equation (2) in the LiBH4-rich composition [13,19]. Our results demonstrate that the reaction between LiBH4 and Mg2FeH6 was stoichiometric and did not degrade when excess LiBH4 or Mg2FeH6 was present.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, in a previous study, we have tried to bring down the dehydrogenation temperature of LiBH 4 by combining it with a transition-metal-based complex hydride, Mg 2 FeH 6 . We ball-milled the two complex hydrides over a large composition range: (1 − x)LiBH 4 + xMg 2 FeH 6 (0.25 ≤ x ≤ 0.9) [12][13][14][15]. The dehydrogenation properties were investigated using a dynamic measurement: thermogravimetry-mass spectrometry (TG-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this mixes the elevated gravimetric hydrogen density of LiBH4 (13.9%) [13] with its impressive volumetric counterpart of Mg2FeH6 (150 g L −1 ) [5]. Other studies on related compounds have also shown similarly great levels of promise [14][15][16][17]. In a study by Li et Al.…”
Section: Namementioning
confidence: 88%
“…Another likely explanation for mutual desorption behavior is the hydrogen exchange of each of the components prior to desorption similar to the system LiBH 4 -Mg 2 FeD 6 . 24 Hydrogen exchange has been shown in the MgH 2 þ LiBH 4 system therefore increasing the desorption temperature of MgH 2 . 25 In simultaneous hydrogen release from all of the RHCs occurred within a narrow temperature release with a single or near single transition.…”
mentioning
confidence: 99%